REKONSTRUKSI PENYELESAIAN SENGKETA PASAR MODAL AKIBAT MANIPULASI INFORMASI OLEH FINFLUENCER DI MEDIA SOSIAL - Emiel Salim Siregar; Melati Anjelika Putri Sinaga; Vivi Indah Mayuni; Sintia Natasya; Putri Viranda Ray; Yoshi Kristine Togi Marito Purba (Smart Education, 2026)
Abstract: This study aims to reconstruct the dispute resolution mechanism in capital markets arising from information manipulation by finfluencers on social media. The rapid growth of digital investors has increased reliance on informal sources, creating legal gaps in accountability and investor protection. This research employs a normative legal method using statute and conceptual approaches by analyzing laws and regulations related to capital markets, financial services, and electronic information. The results indicate that existing dispute resolution mechanisms remain fragmented, reactive, and not fully adaptive to digital-based violations, particularly those involving non-licensed actors such as finfluencers. The absence of clear legal standing and accountability standards complicates the process of evidence, liability determination, and investor recovery. This study proposes a reconstruction model through strengthening regulatory clarity, expanding legal subject recognition, integrating digital evidence frameworks, and optimizing alternative dispute resolution mechanisms. In conclusion, a more adaptive and responsive legal framework is necessary to ensure effective dispute resolution and enhance investor protection in the digital capital market ecosystem. Keywords: Capital Market; Dispute Resolution; Finfluencer; Information Manipulation; Investor Protection. Abstrak: Penelitian ini bertujuan untuk merekonstruksi mekanisme penyelesaian sengketa pasar modal akibat manipulasi informasi oleh finfluencer di media sosial. Pertumbuhan investor digital meningkatkan ketergantungan pada sumber informasi nonformal sehingga memunculkan celah hukum terkait tanggung jawab dan perlindungan investor. Penelitian ini menggunakan metode hukum normatif dengan pendekatan perundang-undangan dan konseptual melalui analisis regulasi pasar modal, jasa keuangan, dan informasi elektronik. Hasil penelitian menunjukkan bahwa mekanisme penyelesaian sengketa yang ada masih bersifat terfragmentasi, reaktif, dan belum adaptif terhadap pelanggaran berbasis digital, terutama yang melibatkan aktor tanpa izin seperti finfluencer. Ketidakjelasan kedudukan hukum dan standar pertanggungjawaban menyebabkan kesulitan dalam pembuktian, penentuan tanggung jawab, serta pemulihan kerugian investor. Penelitian ini menawarkan model rekonstruksi melalui penguatan regulasi, perluasan subjek hukum, integrasi pembuktian digital, dan optimalisasi penyelesaian sengketa alternatif. Simpulan menunjukkan bahwa kerangka hukum yang adaptif diperlukan untuk menjamin penyelesaian sengketa yang efektif dan perlindungan investor di era pasar modal digital. Kata Kunci: Pasar Modal; Penyelesaian Sengketa; Finfluencer; Manipulasi Informasi; Perlindungan Investor